Freezing Fertility Oocyte Cryopreservation and the Gender Politics of Aging - van de Wiel, Lucy (Biopolitics: medicine, technoscience, and health in the twenty-first century series, 2020)
Welcomed as liberation and dismissed as exploitation, egg freezing (oocyte cryopreservation) has rapidly become one of the most widely-discussed and influential new reproductive technologies of this century. In Freezing Fertility, Lucy van de Wiel takes us inside the world of fertility preservation-with its egg freezing parties, contested age limits, proactive anticipations and equity investments-and shows how the popularization of egg freezing has profound consequences for the way in which female fertility and reproductive aging are understood, commercialized and politicized. Beyond an individual reproductive choice for people who may want to have children later in life, Freezing Fertility explores how the rise of egg freezing also reveals broader cultural, political and economic negotiations about reproductive politics, gender inequities, age normativities and the financialization of healthcare. Van de Wiel investigates these issues by analyzing a wide range of sources-varying from sparkly online platforms to heart-breaking court cases and intimate autobiographical accounts-that are emblematic of each stage of the egg freezing procedure. By following the egg's journey, Freezing Fertility examines how contemporary egg freezing practices both reflect broader social, regulatory and economic power asymmetries and repoliticize fertility and aging in ways that affect the public at large. In doing so, the book explores how the possibility of egg freezing shifts our relation to the beginning and end of life.